Sub-Watershed Prioritization for Soil Conservation and Watershed Management Through Geospatial Analysis in Babai Watershed, Dang District, Nepal - Oli, Keshar; Pandey, Kabita (FORESTRY: Journal of Institute of Forestry, Nepal, 2024)
As global environmental challenges such as water scarcity, soil erosion, and habitat degradation continue to escalate, the importance of effective watershed management becomes increasingly evident. Freshwater resources are under mounting pressure, particularly in regions with limited financial and technical capacities, underscoring the necessity of sustainable management practices. One essential approach to achieving this goal is sub-watershed prioritization, which plays a pivotal role in optimizing conservation efforts and resource allocation. This study focuses on prioritizing sub-watersheds within the upper region of the Babai Watershed, located in the Dang District of Nepal, through a GIS-based land use-land system morphometric analysis. The prioritization process integrates biophysical and anthropogenic factors, weighted at 60% and 40% respectively, to assess ten sub-watersheds ranging from 64 to 148 square kilometers. Among these, Gwar Khola emerged as the highest priority sub-watershed, primarily due to its high erosion potential and dense population, while Hapur Khola ranked second and Kaptine Khola ranked lowest. These results emphasize urgent need for targeted interventions in high-priority sub-watersheds, particularly in Gwar Khola, while also advocating for ongoing monitoring and management efforts across all sub-watersheds. By establishing a robust framework for effective resource allocation, this study aims to enhance the long-term resilience of the Babai Watershed, contributing to sustainable watershed management practices in the region.